PENGARUH PELATIHAN PERTOLONGAN PERTAMA KECELAKAAN TERHADAP PENGETAHUAN SISWA KELAS 11 - Candra Patniawati, Candra Patniawati; Wulandari, Tri; Jaelani, Hamdan; Mulana, Mohammad Rizky; Viana; Milkhatun; Rizal, Alfi Ari Fakhrul (Poltekkes Kemenkes Yogyakarta, 2024)
School students frequently experience emergency situations due to accidents, such as fainting, poisoning, bleeding, fractures, and sudden animal bites/stings. Students, teachers, or educational staff often encounter these issues at school. When faced with such an emergency situation, most of them can only panic, unable to do much in providing first aid, leaving the victim lying there and at risk of losing their life without any rescue actions, even just standing by and becoming spectators to the critically ill person who is dying.This study wants to find out what eleventh-grade students at Miftahul Ulum Anggana Private Madrasah Aliyah knew before and after getting first aid training for accidents. It will do this by using a pre-experimental method, a one-group pretest-posttest design, and the Wilcoxon test and the dependent T-test. The results indicate a significant effect (?<0.05) of the first aid training for accidents on the knowledge of eleventh-grade students at Miftahul Ulum Anggana Private Madrasah Aliyah.